2002
DOI: 10.1046/j.1440-172x.2002.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and patients’ perceptions of dignity

Abstract: It is generally agreed in the nursing literature that the maintenance of patient dignity is an important element of nursing care that is highly valued by patients. Despite this, dignity is seldom defined and there are few guidelines that nurses may use in their practice to safeguard individual patients' dignity. This phenomenological study aimed to uncover patients' and nurses' perceptions of dignity, formulate a definition of dignity based on the experience of patients and nurses, and identify nursing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
158
1
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(196 citation statements)
references
References 13 publications
(23 reference statements)
22
158
1
15
Order By: Relevance
“…Providing dignified care also has undeniable effects on health indicators including life expectancy and quality of life (Chochinov et al, 2005). On the other Zoleikha Avestan 1 *, Azad Rahmani 2 , Fatemeh Heshmati-Nabavi 3 , Sima Mogadasian 1 , Safieh Faghani 4 , Arman Azadi 5 , Ali Esfahani 2 hand, violation of patients' dignity may influence their psychological and spiritual status and also adversely affect their cooperation with medical staff (Walsh and Kowanko., 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing dignified care also has undeniable effects on health indicators including life expectancy and quality of life (Chochinov et al, 2005). On the other Zoleikha Avestan 1 *, Azad Rahmani 2 , Fatemeh Heshmati-Nabavi 3 , Sima Mogadasian 1 , Safieh Faghani 4 , Arman Azadi 5 , Ali Esfahani 2 hand, violation of patients' dignity may influence their psychological and spiritual status and also adversely affect their cooperation with medical staff (Walsh and Kowanko., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, factors such as change in living environment, unfamiliar setting and dependence on health care workers significantly affect patients' dignity during hospitalization (Walsh and Kowanko., 2002). The three most significant factors that affect patients' dignity include illness-related concerns, personal and social factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Therefore, the concept of dignity is acknowledged as a core aspect of nursing care. [3,7] A review of the literature showed dignity is represented in a variety of words and seems a complex concept with various attributes. Overall, dignity is about empowering patients by enhancing patients' positive identity and recognize and sustain their own, distinct individuality.…”
Section: Introductionmentioning
confidence: 99%
“…42 The experience of health and illness is affected by culture and religion, and a misunderstanding of cultural difference may create obstacles to providing the best possible treatment. 12 Cultural differences related to draping and physical exposure among cultures such as Aboriginal, 45 Chinese, 20 One might surmise from the above discussion that health care professionals assume they have been sufficiently educated in draping techniques during their entry-level education. However, the perceptions of the recipients of that care suggest that this may not be the case.…”
mentioning
confidence: 99%